IMPLEMENTASI KEBIJAKAN PERATURAN MENTERI AGAMA NOMOR 32 TAHUN 2020 TENTANG MA’HAD ALY: ANTARA HARAPAN DAN DILEMA - Maskuri Maskuri (LP2M Universitas Ibrahimy, 2024)
The enactment of Law Number 18 of 2019 concerning Islamic Boarding Schools, followed by Regulation of the Minister of Religion of the Republic of Indonesia Number 32 of 2020 concerning Ma'had Aly, should be a hope for organizers and managers of education in the Islamic boarding school environment. These hopes include funding support and certainty of Ma'had Aly graduates. In addition, there is a legal guarantee for fulfilling the right to obtain employment opportunities and continue studies to the next level of education. Providing guarantees of recognition, affirmation, and facilitation for Islamic boarding schools based on their traditions and characteristics is a sociological and philosophical consideration when forming Islamic boarding school laws. To date, this guarantee has not been fully realized. The hope of Islamic boarding schools is still accompanied by the dilemma of ensuring recognition from the government. The author is interested in uncovering what the managers of Ma'had Aly are worried about, especially after the implementation of PMA Number 32 of 2020 concerning Ma'had Aly. The researcher's focus is to describe the implementation of these regulatory policies. Because it concerns statutory norms, the method used in this research is normative juridical research, namely, literature study research, to examine PMA 32 of 2020. The aim is to describe the implementation of PMA 32 of 2020 for Islamic boarding schools that organize Ma'had Aly, the problems experienced by the management, and how the Ministry of Religion responds to the Islamic boarding school's hesitation in implementing recognition, affirmation and facilitation policies. As a result, there are still problems for the organizers of Ma'had Aly. The external quality assurance system through the community assembly has not shown its productivity. The government, in this case, the Ministry of Religion, needs to be encouraged to have the courage to take strategic policy steps as a concrete form of recognition, affirmation and facilitation of Ma'had Aly implementation policies. Apart from that, the government is also encouraged to form a directorate general of Islamic boarding schools to solve bureaucratic problems in Islamic boarding school services.